Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4161/fly.22687
|View full text |Cite
|
Sign up to set email alerts
|

Sex, stem cells and tumors in the Drosophila ovary

Abstract: The Drosophila Sex-lethal (Sxl) gene encodes a female-specific RNA binding protein that in somatic cells globally regulates all aspects of female-specific development and behavior. Sxl also has a critical, but less well understood, role in female germ cells. Germ cells without Sxl protein can adopt a stem cell fate when housed in a normal ovary, but fail to successfully execute the self-renewal differentiation fate switch. The failure to differentiate is accompanied by the inappropriate expression of a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Therefore, it has been proposed that Sxl partners with newly-expressed Bam in cystoblasts to promote differentiation by antagonizing nanos and likely other genes required to maintain GSCs [ 34 36 ]. Since bam itself provides cell-type specificity [ 78 ], we suggest that the increased fertility of Wolbachia -infected Sxl mutants is a result of increased bam activity driving the differentiation of GSCs, rather than a direct effect on Sxl activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been proposed that Sxl partners with newly-expressed Bam in cystoblasts to promote differentiation by antagonizing nanos and likely other genes required to maintain GSCs [ 34 36 ]. Since bam itself provides cell-type specificity [ 78 ], we suggest that the increased fertility of Wolbachia -infected Sxl mutants is a result of increased bam activity driving the differentiation of GSCs, rather than a direct effect on Sxl activity.…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Michael M. Shen ( Columbia University Medical Center, New York, NY, USA ) showed that luminal cells are favored as the cell of origin for mouse prostate cancer by lineage tracing (14). Dr. Helen Salz ( Case Western Reserve University, Cleveland, OH, USA ) presented her work describing the tumor suppressing role of the female specific RNA binding protein SXL and the oncogenic role of testis-specific chromatin reader Phf7 in Drosophila ovary stem cells (15). Dr. Zhenghe John Wang (Case Western Reserve University, Cleveland, OH, USA) reported that that the loss of the tumor suppressor tyrosine phosphatase PTPRT in intestinal stem cells makes these cells more proliferative through activating STAT3 (pY705) (16).…”
Section: Genetics Epigenetics and Rna Regulators Of Cscsmentioning
confidence: 99%
“…Austin Gurney (OncoMed Pharmaceuticals, Redwood City, CA, USA) targeted the stem cell pathways of Notch, Wnt and RSPO in cancer treatment using Demcizumab (anti-Notch ligand DLL4 antibody), OMP-52M51 (anti-Notch1), and OMP-18R5 (anti-Wnt receptor FZD monoclonal antibody) in combination with chemotherapeutic agents on cancers of pancreas, lung, breast, and colon (65). Dr. Sanford Markowitz (Case Western Reserve University, Cleveland, OH, USA) identified the TGFβ-regulated metabolic tumor suppressor 15-prostaglandin dehydrogenase (15–PGDH) pathway in colon tumorigenesis and discussed its clinical translation. Dr. Lyndsay Harris (Case Western Reserve University, Cleveland, OH, USA) and her team discovered a basal-like group of HER2 tumors with a stem-cell-like, EMT phenotype that are more resistant to Herceptin.…”
Section: Clinical Trials Of Csc Targeting Therapeuticsmentioning
confidence: 99%
“…This condition or K d represents the most sensitive part of the RNA-binding curve. 4. Incubate the protein binding reaction for 20-30 min at 25 °C (or on ice).…”
Section: Synthesis Of Rnamentioning
confidence: 99%
“…The Drosophila protein Sex-lethal (SXL) or the master sex-switch protein is absent in males, but present in females. It recognizes uridine-rich sequences or pyrimidine-tracts adjacent to specific splice sites in downstream pre-mRNA targets (transformer, Sex-lethal, and male-specific lethal2) in somatic cells 1,2,3,4 . In addition, it regulates polyadenylation site switching by binding to uridine-rich polyadenylation enhancer sequences in the enhancer of rudimentary (e(r)) transcript 5,6 .…”
Section: Introductionmentioning
confidence: 99%